Efek Ekstrak Daun Sambung Nyawa (Gynura procumbens) untuk Mengurangi Ketombe pada Kulit Kepala - Neneng Siti Silfi Ambarwati; Rita Susesty; Devi Sulastiowati (Fakultas Farmasi Universitas Pancasila, 2021)
Gynura procumbens is a medicinal plant commonly used in Asian countries such as China, Thailand, Indonesia, Malaysia, and Vietnam. G. procumbens content ﬂavonoids and glycosides and have bacteria activity and anti-fungal activity such as Candida albicans and Aspergillus niger. The purpose of this study was to obtain empirical data about the eﬀect of using the G. procumbens leaves extract on reducing dandruﬀ on the scalp. The extract was obtained by the maceration method using 70% ethanol solvent. The phytochemical compound content is determined with spectrophotometry ultraviolet. Two observers observe the scalp by using observation sheets and grating instruments assisted by a skin and hair analyzer. The reduction of scalp dandruﬀ was the diﬀerence between the initial the results and the ﬁnal test (after treatment). The sample was selected using a purposive sampling technique totaling ten people and divided into two groups (experimental and control groups). The results showed that the calculation of hypothesis testing after analyzing the data obtained a value of t count (5.817)>t table (1.86). This showed an eﬀect of using the G. procumbens leaves extract as a shampoo for reducing dandruﬀ on the scalp. The use of G. procumbens leaves extract as shampoo can reduce dandruﬀ.